20-Hydroxy- and 20-carboxy-leukotriene (LT) B4 downregulate LTB4-mediated responses of human neutrophils and eosinophils. Issue 6 (24th January 2019) - Archambault, Anne-Sophie; Poirier, Samuel; Lefebvre, Julie-S; Robichaud, Philippe-Pierre; Larose, Marie-Chantal; Turcotte, Caroline; Martin, Cyril; Provost, Véronique; Boudreau, Luc H; McDonald, Patrick P; Laviolette, Michel; Surette, Marc E; et al.
Abstract: Leukotriene B4 (LTB4 ) plays a prominent role in innate immunity as it induces phagocyte recruitment, the release of antimicrobial effectors, and as it potentiates the ingestion and killing of pathogens. In humans, LTB4 has a short half-life and is rapidly metabolized by leukocytes, notably into 20-OH- and 20-COOH-LTB4 by neutrophils. Although these LTB4 metabolites bind to the BLT1 receptor with high affinity, they activate neutrophils to a much lower extent than LTB4 . We thus postulated that LTB4 metabolites could dampen BLT1 -mediated responses, therefore limiting the impact of LTB4 on human neutrophil functions. We found that 20-OH-LTB4 and 20-COOH-LTB4 inhibited all of the LTB4 -mediated neutrophil responses we tested (migration, degranulation, leukotriene biosynthesis). The potencies of the different compounds at inhibiting LTB4 -mediated responses were 20-OH-LTB4 = CP 105, 696 (BLT1 antagonist) > > 20-COOH-LTB4 ≥ resolvin E1 (RVE1 ). In contrast, the fMLP- and IL-8-mediated responses we tested were not affected by the LTB4 metabolites or RVE1 . 20-OH-LTB4 and 20-COOH-LTB4 also inhibited the LTB4 -mediated migration of human eosinophils but not that induced by 5-KETE. Moreover, using 20-COOH-LTB4, LTB4, and LTB4 -alkyne, we show that LTB4 is a chemotactic, rather than a chemokinetic factor for both human neutrophils and eosinophils. In conclusion, our data indicate that LTB4 metabolites and RVE1 act as natural inhibitors of LTB4 -mediated responses. Thus, preventing LTB4 ω-oxidation might result in increased innate immunity and granulocyte functions.